Fabry-Perot Interferometer Based on Suspended Core Fiber for Detection of Gaseous Ethanol - Paixão, Tiago (2022)
An optical fiber tip sensor based on a Fabry-Perot interferometer is proposed for the detection of ethanol in the gas phase. The sensor is fabricated by fusion splicing one end of the suspended core fiber to a single mode fiber, whereas the other end is kept open to enable the interaction between the light propagating in the suspended core and the ethanol gas molecules. The sensor was tested with different percentages of ethanol, exhibiting a linear response between 0 and 100 wt.%, with a sensitivity of 3.9 pm/wt.%. The proposed sensor, with a length of a few hundred micrometers, can be an alternative solution for the detection of gaseous ethanol in foods or beverages, such as wines and distilled drinks